First evidence of testate amoebae in Lago Fagnano (54° S), Tierra del Fuego (Argentina): Proxies to reconstruct environmental changes - Caffau, Mauro (2015)
We report here the first findings of testate amoebae at high southern latitudes (54° S) from four gravity cores recovered in the Lago Fagnano (Tierra del Fuego, Argentina), where twelve taxa have been recognized. Among them, Centropyxis constricta “constricta”, Centropyxis elongata, Difflugia globulus, Difflugia oblonga “oblonga”, and Difflugia protaeiformis “amphoralis” are always present, while other taxa are randomly distributed. According to the sand/silt ratio in the different cores, the Total Organic Carbon content and the Carbon/Nitrogen ratio, as well as the presence/disappearance and abundance of testate amoebae from cluster analysis, we infer a correlation between major textural/granulometrical changes found in the cores and environmental changes. A seismic event occurred on 1949, which substantially modified the morphology of the eastern Lago Fagnano shoreline and the supply pattern from two main eastern tributaries of the lake, is recorded in the studied cores. This event has in part modified the distribution of testate amoebae taxa within the studied cores. Present results show that testate amoebae represent important indicators to detect changes occurring in the environment in which they live.